Evolution of bi-Gaussian surface parameters of silicon-carbide and carbon-graphite discs in a dry sliding wear process. (August 2017) - Hu, Songtao; Brunetiere, Noel; Huang, Weifeng; Liu, Xiangfeng; Wang, Yuming
Abstract: A surface-surface dry sliding wear of silicon-carbide and carbon-graphite discs is performed on a rotational tribological tester. Coefficient of friction ( COF ) is monitored as a function of time. Samples are measured by a white light interferometer. Four uniform groups, each with two repetitions, are set to different test durations to investigate the evolution of bi-Gaussian surface parameters in a wear process. The results show that the hard sample has a smoothed upper component with time, but a slightly changed lower component due to wear-generated debris. The wear-generated debris, however, introduce deep scratches to the soft sample before its upper component being altered, yielding a sharp lower component. Furthermore, the correlation between bi-Gaussian surface parameters and COF is explored. Highlights: Evolution of bi-Gaussian surface parameters in a dry sliding wear process is investigated. Silicon carbide and carbon graphite, widely used in mechanical face seals, are selected. Correlation between bi-Gaussian surface parameters and coefficient of friction is explored.